Log??stica interna dos res??duos s??lidos de servi??os de sa??de: um estudo de caso do hospital p??blico "x" na cidade de S??o Paulo - Lee, Milly Man Hwa (2017)
The problems and concerns involving Solid Waste from Healthcare Services (RSSS), though an old issue, are still very troubling today. Incorrect disposal of solid waste is a major concern, especially in hospital, in that it poses a risks of contamination from infectious diseases to patients, visitors, as well as individuals who indirectly handle such waste, be it healthcare providers or cleaning staff. Mindful of the complexity of RSSS classifications and segregation in hospitals, this dissertation aims at analyzing the RSSS internal logistics currently in place and puts forth a new process to optimize waste collection - from intermediate area and external storage - placing each actor and their social responsibilities so that the infectious and common waste do not mix; and devise internal means to reduce generation of waste right at the source up to the final disposal. The data obtained shows how difficult RSSS management is when it comes to correctly segregation providers find it difficult to properly separate waste and attend training on the significance of RSSS and hospitals' administrators need to have a solid grasp of the relevance of waste segregation, as they still prioritize health care of the population to the detriment of allocating funds for the management activities of the RSSS. The methodology used was the case study of a Public Hospital located in the city of S??o Paulo, data was collected via non-participatory observation, informal interview, records and information was obtained from scientific papers and congresses on Scopus, Scielo and Google Scholar. The theoretical contribution of this research is a tool to analyze the logistics involving hospital waste, so that they are meet the standards required under legal standards and rules and a practical contribution applied in bringing Hospital "X" to compliance with applicable rules and regulations in a realistic manner and at low cost and without causing major interferences with hospital's daily operation.